Winter swimming – is it possible to develop adaptation to cold temperature? A literature review - Brzoza, Martyna; Stawińska-Dudek , Julia; Buras , Barbara; Orzeł, Milena; Orzeł, Bartłomiej; Aboud, Ali; Józefowicz, Wiktoria; Bielecka, Aleksandra; Dubniański, Bartosz; Stawińśka, Kornelia (Journal of Education, Health and Sport, 2025)
Introduction and purpose Over the years winter swimming has gained popularity, becoming an eagerly practiced form of physical activity. This review aims to examine its influence on the human organism and explore the mechanisms of adaptation developed by winter swimmers. Materials and methods This work is based on the analysis of the materials obtained from “PubMed” and “Google Scholar” scientific databases using the key words selected based on their relevance to examining the matter in subject, such as: cold adaptation, cold water immersion, ice swimming, hypothermia, winter swimming The state of knowledge Investigated studies indicate that winter swimming influences human organism in various aspects, having a completely different impact depending on previous cold-water exposures, health status and individual adaptation. Winter swimmers tend to develop a wide range of compensatory mechanisms including hormonal, metabolic and immunological changes, improved thermoregulation and enhanced antioxidative protection. In contrast, for unadopted individuals cold water immersions may lead to severe complications including hypothermia and even fatal consequences. Conclusions Winter swimmers develop mechanisms of cold adaptation that enable them to perform and benefit from such activity. However, proper adjustment, following preventive measures and guidelines such as gradual, regular adaptation, warm-up exercises and being aware of individual health status are vital to minimize detrimental effects that concern especially inexperienced individuals.